PERBANDINGAN EFEKTIVITAS ANTARA TUTOR DOSEN DAN TUTOR MAHASISWA PADA PELAKSANAAN TUTORIAL DENGAN PROBLEM BASED LEARNING DI FAKULTAS KEDOKTERAN UNIVERSITAS HASANUDDIN - ASRIYANI, SRI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Introduction. Problem Based Learning (PBL) method requires tutors to facilitate the learning process. High demand on tutor which do not match with tutor availability will increase the need for alternative tutor source. Research about using senior students as tutor (peer tutoring) have been done by using complex instrumentation which is hard for the students to make evaluation. Objective. To compare the effectiveness of staff/lecturer and student in facilitating tutorial process and students’ achievement Method. This research is an quasi experimental research by using nonequivalent control group design. The data was taken from 18 groups of students which is facilitated by tutors from staff and students. Data analysis was done by using t-test to compare the effectiveness and achievement of the students. Result. The research involve 165 students in 18 different tutorial groups, nine groups were facilitated by staff and nine other groups were facilitated by students. The effectiveness of the tutors was measured by the tutor’s ability to trigger an active and constructive learning process, their availability to trigger self-directed learning, facilitating contextual learning process, facilitating a colaborative learning process and interpersonal behaviour. The result of this research shows that majority of them agree and strongly agree about the points measured in either staff tutors or student tutor group. The t-test to compare effectiveness of staff and student tutor on constructive/active larning, self-directed learning, contextual learning, collaborative learning, and intra-personal behaviour gave p>0.05 points. The students achievement (difference in pre and post test) which is facilitated by staff tutor are better than the group facilitated by student tutor with ttest point of p<0.05. Conclusion. There is no difference in effectiveness of staff and student tutor in tutorial process of 1 modul in Medical Faculty Hasanuddin University and there is difference in student’s achievements, which the group facilitated by staff tutor have more and higher achievements than those facilitated by student tutor.